Challenges and Novelties in the Treatment of Obesity in Adults. A review - Kuczapska, Karolina; Kurowski, Marek; Gliwa, Anna; Ryglewicz, Monika; Fabian, Dariusz; Leszczyńska-Knaga, Elżbieta; Jakubczyk, Natalia; Rutkowska-Kawalec, Weronika; Moczydłowski, Paweł; Michalczuk, Karolina (Journal of Education, Health and Sport, 2025)
Introduction Obesity is a complex, chronic disease that continues to be a significant global health challenge due to its prevalence and association with numerous comorbidities. Etiology of this disease includes different factors from genetic, environmental, and lifestyle fields, while effective management of obesity is still being studied. Aim of the study The aim of this comprehensive review is to examine arising innovations in the treatment of adult obesity. Deeper insight into the available database would help to provide better understanding of obesity and of its treatment. Materials and Methods To reach satisfying results the research was conducted on the articles referring to obesity treatment from the Pubmed databases. Articles from recent years were preferably utilized to keep the review up to date. Results Nowadays, pharmacotherapy can offer GLP-1 receptor agonists like liraglutide or semaglutide, and new drugs like tirzepatide that show great effectiveness. Additionally, bariatric surgery continues to offer great solution for severe obesity, combining restrictive and malabsorptive mechanisms for significant weight loss and metabolic benefits. The main procedures include gastric bypass with sleeve gastrectomy or duodenal switch. Personalized treatment, referring to different obesity phenotypes, has shown improvement in the therapeutic outcomes. Some new therapies are studied including triple agonists (retatrutide), non-peptide GLP-1 receptor agonists, and drugs reaching other receptors. All of them are promising for the effective obesity treatment in the future. Summary This review underlines the need for multidisciplinary and personal approach in the treatment of obesity and the need to share the knowledge about it to address the growing obesity epidemic effectively. Recognizing obesity as a chronic and complex disease is essential to improve patient’s understanding of their condition as well as to reach effective treatment outcomes.